Assessment of Cutting Size and Exogenous Hormone Treatment on Sprouting and Rooting Potential in the Indo-Pacific Multipurpose Legume Tree-Parkia timoriana (DC.) Merr. - Singh, Manish Kumar; Borpuzari, Papori; Ankasaikia, Priy (Indian Forester, 2023)
Different hormonal treatment and their interaction with stem cutting sizes on sprouting, rooting potential and subsequent transplanting survival percentage of the commercially important multipurpose legume tree Parkia timoriana were investigated. The study was conducted in partially controlled environment with two factorial treatments considering factor A cutting size (long cuttings: length-20-25 cm; dia. 2-2.5 cm with 4-5 nodes and mini cuttings: length-15-20 cm; dia. 1-1.5 cm with 1-2 nodes) and factor B rooting hormone in different concentrations [Indole-3-butyric acid (IBA), Naphthalene Acetic Acid (NAA) and Indol-3- Acetic acid (IAA)] in 50 ppm, 100 ppm and 200 ppm, while the untreated cuttings were used as control. 30 cuttings of each size bearing desired number of buds were planted in polybag (sand, soil and FYM in 1:1:1 ratio) for each treatment. In present study, long cutting of Parkia significantly enhance the sprouting parameters i.e. days to sprout, sprout length, sprout diameter, as well as rooting parameters i.e. root length, rooting percentage. Also, long cuttings have higher transplanting survival percentage as compared to mini cuttings. Long cuttings treated with IBA 200 ppm significantly improved survival percentage (87%) and rooting percentage (60-75%) followed by NAA (200 ppm) as compared to other treatments. In addition, the impact of different hormonal concentration on survival percentage and rooting percentage for mini cuttings were significantly very low compared to long cuttings. Thus, it is advisable to use long cuttings, along with application of IBA (200 ppm) and NAA (200 ppm) for propagating of P . timoriana through stem cutting.